Diretrizes para implantação de uma unidade de controladoria no município de Sobral - Macêdo, Francisca Francivânia Rodrigues Ribeiro (2010)
Because of new legal requirements imposed on municipal mangers, the growing population's demand asking for the quality of public services and also the search of ethics and transparency in government actions appears the need of deploying units of controllership at the Local Governments in order to assist these managers in the use of public resources and compliance with legal regulations. The Controllership presented as an efficient way of achieving results and goals set by managers doing so through the use of efficient operating systems, regular auditing and standardization of activities. This environment requires from local governments based on the implementation of consistent controls that was found a lack of a Controllership unit in Sobral. This study has as main purpose propose directions to create a Controllership unit to Sobral. Thus, this scientific investigation has a qualitative method since it searched to find subsidies for this proposal. The methodology used in this research was characterized as an exploratory case study, and has used also an extensive bibliographical and documental research. It was observed in this study the fact that the City of Sobral has not a system of internal control structured being all activities in the budgetary and financial plan centralized in the central computer system called Phoenix. After a deep study and data analysis coming from a semi-structured interview applied to three managers, sought to outline guidelines for the implementation of the Controllership to the City of Sobral. It was concluded that currently exists in the City of Sobral an efficient operating structure system, the processes need to be better monitored and the most utilized information generated and most importantly, that is perfectly feasible to create the Controllership in the city under study since it has an administrative structure and physical and able to deploy effectively, efficiency and effectiveness of such a unit.